Investigation of chemical changes in sealers during application of the warm vertical compaction technique - Viapiana, R. [UNESP]; Baluci, C. A.; Tanomaru-Filho, M. [UNESP]; Camilleri, J. (Wiley-Blackwell, 2015)
Aim To assess (i) heat generated by pluggers during warm vertical compaction of gutta-percha and investigation of temperature changes on the external root surface during canal filling, and (ii) the chemical changes of root canal sealers induced by heat.Methodology Four sealers, namely AH Plus, MTA Plus and two other experimental sealers based on tricalcium silicate, were characterised. External temperatures generated on the root surface during warm vertical compaction of gutta-percha with different sealers inside the root canal were monitored using an infrared thermography camera. Chemical changes induced by heating the sealers were assessed by Fourier transform infrared (FT-IR) spectroscopy.Results MTA Plus and the experimental sealers were composed of a cement and radiopacifier, with epoxy resin or a water-soluble polymer as dispersant, whilst AH Plus was epoxy resin-based. The heat generated at the tips of the continuous wave pluggers was found to be lower than the temperature set and indicated on the device LCD display. The sealers reduced the heat generated on the external root surfaces during the heating phase. AH Plus sustained changes to its chemical structure after exposure to heat, whilst the other sealers were unaffected.Conclusions The temperatures recorded at the tips of continuous wave pluggers varied with their taper and were lower than the temperature set on the System B LCD display. Root canal sealers reduced the dissipation of heat generated during warm vertical compaction, with the temperature at the external root surface maintained at 37-41 degrees C, a temperature below that is necessary to cause irreversible damage to bone and periodontium. The use of AH Plus sealer during warm vertical compaction techniques results in chemical changes in the sealer. The effect on sealer properties needs to be further investigated.
Keywords: AH Plus; characterisation; MTA Plus; root canal obturation; root canal sealers; System B